APPARATUS AND METHOD FOR PROVIDING AN ATOMIC SET OF DATA ACCESSES (2017)
A data processing apparatus includes a cache memory for storing data items to be accessed. Coherency control circuitry controls coherency between data items stored within the cache memory and one or more other copies of the data items stored outside the cache memory. A data access buffer buffers a plurality of data access to respective data items stored within the cache memory. Access control circuitry is responsive to coherency statuses managed by the coherency control circuitry for the plurality of data items to be subject to data access operations to be performed together atomically as an atomic set of data accesses to ensure that the coherency statuses for all of these data items permit all of the atomic set of data accesses to be performed within the cache memory before the set of atomic data accesses are commenced.